Faktor – Faktor yang Mempengaruhi Financial Performance Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia - Kartika, Nurmaya; Prilia, Anastasia Arum Gerda; Anggitia, Ajeng; Amilawati, Salsabillah; Leon, Farah Margaretha (Universitas Hamzanwadi, 2024)
This study aims to identify variables that affect financial performance in state-owned companies (SOEs) listed on the IDX. The addition of asset utilisation variable as an independent variable is a novel part of this study. This research method involves collecting data from 20 state-owned companies over a five-year period (2018-2022), and applying data processing analysis using panel data regression analysis techniques. The results found that foreign ownership has a negative impact on ROA and ROE, while state ownership has a negative impact on ROA. In contrast, leverage moderated by foreign ownership has a positive effect on ROA and ROE. Asset utilisation also positively affects ROA but has a negative impact on ROE. In addition, liquidity, tangibility, sales growth, age have an effect on financial performance. The implication for financial managers is to choose the best way to utilise assets in order to achieve business objectives, especially to improve shareholder welfare. This research emphasises how important ownership structure and liquidity are for investors when choosing investment opportunities in state-owned companies.